Stimulation of angiogenesis by cilostazol accelerates fracture healing in mice. Issue 12 (7th July 2015) - Herath, Steven C.; Lion, Thorsten; Klein, Moritz; Stenger, David; Scheuer, Claudia; Holstein, Jörg H.; Mörsdorf, Philipp; Rollmann, Mika F.R.; Pohlemann, Tim; Menger, Michael D.; Histing, Tina
ABSTRACT: Cilostazol, a selective phosphodiesterase‐3 inhibitor, is known to control cyclic adenosine monophosphate (c‐AMP) and to stimulate angiogenesis through upregulation of pro‐angiogenic factors. There is no information, however, whether cilostazol affects fracture healing. We, therefore, studied the effect of cilostazol on callus formation and biomechanics during fracture repair. Bone healing was analyzed in a murine femur fracture stabilized with an intramedullary screw. Radiological, biomechanical, histomorphometric, histochemical, and protein biochemical analyses were performed at 2 and 5 weeks after fracture. Twenty‐five mice received 30 mg/kg body weight cilostazol p.o. daily. Controls ( n = 24) received equivalent amounts of vehicle. In cilostazol‐treated animals radiological analysis at 2 weeks showed an improved healing with an accelerated osseous bridging compared to controls. This was associated with a significantly higher amount of bony tissue and a smaller amount of cartilage tissue within the callus. Western blot analysis showed a higher expression of cysteine‐rich protein 61 (CYR61), bone morphogenetic protein (BMP)‐4, and receptor activator of NF‐kappaB ligand (RANKL). At 5 weeks, improved fracture healing after cilostazol treatment was indicated by biomechanical analyses, demonstrating a significant higher bending stiffness compared to controls. Thus, cilostazol improves fracture healing by accelerating both bone formation and callus remodeling. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1880–1887, 2015.